2021
DOI: 10.1186/s12864-021-07612-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of AGXT2 variants on blood pressure and blood sugar among 750 older Japanese subjects recruited by the complete enumeration survey method

Abstract: Background Alanine:glyoxylate aminotransferase 2 (AGXT2; EC 2.6.1.44) is the only enzyme that degrades the R-form of 3-aminoisobutyrate, an intermediate metabolite of thymine. AGXT2, as well as diaminoarginine dimethylaminohydrolase 1 (DDAH1; EC 3.5.3.18), works as an enzyme that degrades asymmetric dimethylarginine (ADMA), which competitively inhibits the nitric oxide synthase family. Thus, these two enzyme activities may change vascular vulnerability for a lifetime via the nitric oxide (NO) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…In Table 2, the missense variant of rs37369 [30] has been shown to be one of the 4 functional SNPs of AGXT2, which has been reported to have strong associations with several cardiorenal traits, such as coronary heart disease [31]. Its significant association with hypertension was very recently reported via multiple regression analysis involving only several targeted SNPs [32]. The missense variant rs11575542 was very recently identified as a functional variant of the DOPA Decarboxylase ( DDC ) gene during the systematic polymorphism screening across the 15-Exon DCC locus [33].…”
Section: Resultsmentioning
confidence: 99%
“…In Table 2, the missense variant of rs37369 [30] has been shown to be one of the 4 functional SNPs of AGXT2, which has been reported to have strong associations with several cardiorenal traits, such as coronary heart disease [31]. Its significant association with hypertension was very recently reported via multiple regression analysis involving only several targeted SNPs [32]. The missense variant rs11575542 was very recently identified as a functional variant of the DOPA Decarboxylase ( DDC ) gene during the systematic polymorphism screening across the 15-Exon DCC locus [33].…”
Section: Resultsmentioning
confidence: 99%
“…SNP rs37370, but not rs37369 or rs180749, and the aforementioned CAAA haplotype were significantly related to carotid atherosclerosis in a study of 1,426 Japanese individuals (10). Another study of 750 older Japanese adults showed that SNP rs16899974 and the CAAA haplotype, but not rs37370, rs37369 or rs180749, were significantly associated with diastolic blood pressure, and that rs16899974, but not rs37370, rs37369, rs180749 or the CAAA haplotype, was significantly associated with casual blood sugar (13). In another Chinese caseecontrol study of 942 patients with coronary heart disease and 1,103 controls, rs37369 was not independently related to coronary heart disease (17).…”
Section: Discussionmentioning
confidence: 98%
“…In a German study, plasma concentrations of SDMA, but not ADMA, were higher in those heterozygous or homozygous for the minor allele of rs37369, whereas no such positive relationship was found between rs16899974 and plasma concentrations of ADMA or SDMA (8). AGXT2 SNPs have also been shown to be related to the following vascular conditions and diseases and related biological data: coronary artery disease (7); heart rate variability (9); carotid atherosclerosis (10); atrial fibrillation (11); chronic heart failure (12); and blood pressure, blood sugar and blood creatinine (13).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As AGXT2 degrades both ADMA and SDMA, whilst DDAH is inactive towards SDMA, this pattern of metabolite changes in plasma would be consistent with downregulation of DDAH in hypoxia, as has been shown experimentally, and compensatory upregulation of AGXT2. In a recent study in 750 elderly Japanese individuals, a loss-of-function haplotype comprising four SNPs in AGXT2 was positively associated with blood pressure and serum glucose levels; individuals homozygous for this haplotype had significantly elevated ADMA levels [35]. Thus, the physiological and pathophysiological roles of AGXT2 in dimethylarginine metabolism in humans require further study.…”
Section: Discussionmentioning
confidence: 98%